2009
DOI: 10.1249/mss.0b013e3181a55200
|View full text |Cite
|
Sign up to set email alerts
|

Running Biomechanics and Lower Limb Strength Associated with Prior Hamstring Injury

Abstract: Although swing phase biomechanics of submaximal sprinting were similar between limbs, the previously injured hamstrings did display significant weakness eccentrically. Residual eccentric weakness may predispose this muscle group to reinjury during late swing, compared with the uninjured limb, because the functional eccentric demand on both limbs was similar. Furthermore, the EH/CHF ratios may better reflect muscle function during sprinting, having the potential to influence rehabilitation to prevent reinjury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 35 publications
5
73
0
12
Order By: Relevance
“…13,16 The percentage difference in eccentric strength between limbs, reported here in the injured cohort (15%), is similar to previously reported data using isokinetic dynamometry (11%-13%). 13,16 It may be argued that it would have been appropriate to normalize the force measurements derived from the experimental device to the stature and weight of the participant. However, we did not believe that this would be critical.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…13,16 The percentage difference in eccentric strength between limbs, reported here in the injured cohort (15%), is similar to previously reported data using isokinetic dynamometry (11%-13%). 13,16 It may be argued that it would have been appropriate to normalize the force measurements derived from the experimental device to the stature and weight of the participant. However, we did not believe that this would be critical.…”
Section: Discussionsupporting
confidence: 90%
“…20,23 Lower eccentric knee flexor strength has been reported as a risk factor for future HSI, 8,19 indicating the importance of eccentric strength for HSI avoidance. 3,18 Further, previously strained hamstrings display reduced levels of eccentric knee flexor strength compared to those in the uninjured contralateral limb, 7,13 which may partially explain why a previous HSI is the primary risk factor for future injury. 2 Currently, the gold standard measure for the assessment of eccentric knee flexor strength is isokinetic dynamometry.…”
mentioning
confidence: 99%
“…Biomechanical research into endurance running has been extensive and mostly concerned 23 with examining the mechanisms of, and potential for overuse injury rather than 24 performance (Buist et al, 2010;Lee, Reid, Elliott, & Lloyd, 2009;Novacheck, 1998). The 25 popularity of endurance running as a recreational activity continues to be high and almost 26 every city in Western society has its own marathon and recreational running events (Bus, 27 2003).…”
Section: Introduction 21 22mentioning
confidence: 99%
“…It is noteworthy that some prospective studies have shown no association between isokinetic knee flexor strength and risk of future HSI (Bennell et al, 1998;Yeung et al, 2009). The level of between-limb knee flexor strength imbalance and the contribution of other muscles during the terminal swing phase are areas of future research given these are known to influence running mechanics (Lee et al, 2009).…”
Section: Hamstring Muscle Weakness and Between Limb Strength Imbalancementioning
confidence: 99%
“…There have been a number of retrospective observations made in relation to the maladaptations following injury, such as; the formation of non-functional scar tissue which impacts muscle tissue lengthening mechanics (Silder, Reeder, & Thelen, 2010), reduced flexibility (Jonhagen, Nemeth, & Eriksson, 1994), chronic reductions in eccentric strength (Croisier et al, 2002;Jonhagen et al, 1994;Lee, Reid, Elliott, & Lloyd, 2009), chronic atrophy of the injured muscle (Silder et al, 2008), alterations in the angle of peak torque (Brockett, Morgan, & Proske, 2004) and lower limb biomechanics (Verrall et al, 2001), however, given the lack of prospective evidence it is difficult to determine if these factors are the cause of or the result of initial injury (Opar et al, 2012).…”
Section: Previous Injurymentioning
confidence: 99%